Transformer vs. RASA model: A thorough attempt to develop conversational Artificial Intelligence to provide automated services to university disciples - Zahir, Shafkat; Roy, Prateeti Saha; Ridita, Humaira Tasnim; Hossain, Tamanna (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.